2020
DOI: 10.1111/cch.12828
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment in early treated HIV‐infected infants participating in a developmental stimulation programme compared with controls

Abstract: Background Neurodevelopmental stimulation programmes can improve developmental outcomes. Antiretroviral therapy (ART) started soon after birth potentially limits the invasion of HIV into the central nervous system. A combination of developmental stimulation and early ART initiation may reduce developmental delays in children with perinatally acquired HIV infection. Methods At a single site in Johannesburg, South Africa, we enrolled 36 HIV‐infected neonates on ART into an intervention group (IG) participating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…67 Many people living with HIV and disabilities can benefit from community-based rehabilitation, rehabilitation, assistive technology and other specialised services. 37,[68][69][70][71][72][73] Multidisciplinary services are therefore needed, ideally near the community, to support the range of impairments connected to HIV. 38,40 However, these services are woefully lacking, particularly in Africa where HIV prevalence is highest, although efforts are underway to scale-up rehabilitation services at a global level.…”
Section: Developing Inclusive Hiv Systems: Good Practice Examplesmentioning
confidence: 99%
“…67 Many people living with HIV and disabilities can benefit from community-based rehabilitation, rehabilitation, assistive technology and other specialised services. 37,[68][69][70][71][72][73] Multidisciplinary services are therefore needed, ideally near the community, to support the range of impairments connected to HIV. 38,40 However, these services are woefully lacking, particularly in Africa where HIV prevalence is highest, although efforts are underway to scale-up rehabilitation services at a global level.…”
Section: Developing Inclusive Hiv Systems: Good Practice Examplesmentioning
confidence: 99%
“…Approximately 1.7 million children live with HIV globally ( 6 ). Kenya is one of the SSA countries with a high burden of HIV ( 7 ) with an average prevalence of 4.8% and an estimated 1.4 million people living with the disease ( 8 ). Among those living with HIV, approximately 83,000 are children aged 0–14 years ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, with early intervention the adverse effects of HIV can be mitigated. For instance, a study conducted by Strelau and colleagues in South Africa demonstrated that implementing a neurodevelopmental stimulation intervention for CHEI treated early CHEI resulted in a significant reduction in neurodevelopmental delays ( 7 ). These findings suggest that early initiation of ART alongside other early childhood stimulation programs has the potential to significantly enhance child developmental outcomes.…”
Section: Introductionmentioning
confidence: 99%